La mendicidad de menores de edad como consecuencia del COVID–19 en la ciudad de Ambato, primer trimestre 2022. - Poma Gómez, Gina Paulina (2023)
The proposed research work arises from the social problems that the most vulnerablegroup of society is experiencing, such as minors, due to the Covid-19 pandemic, which causedgreat havoc worldwide in various aspects that violate the rights enshrined in the Constitution of the Republic of Ecuador, being the Ecuadorian state in charge of ensuring the safety of thispriority group. Begging is a social state to which minors are exposed, holding hands with various harmful aspects, which can lead to other violations of the obligations to which government entities are subject. The revision of the regulations that are in force within the Ecuadorian territory is a fundamental pillar for the same organizations that must rely on all legal bodies to be applied objectively within the framework of legality to obtain all possible guarantees in favor of this priority group in a situation of vulnerability. The methodology to use Quantitative is associated with the positivist tradition, which conceives social reality as an objective structure. The facts or social phenomena studied in this work are measurable and quantifiable. KEYWORDS: Begging, exploitation, covid-19, minors, vulnerable groups.